(untitled) (Journal of Mathematical Study, 2024)
In this paper we obtain the boundedness of non-regular pseudo-differential operators with symbols in Besov spaces on matrix-weighted Besov-Triebel-Lizorkin spaces. These symbols include the classical Hörmander classes.